"Frog Search": Synonymy of Phrynobatrachus nigripes Pickersgill, 2007, plus other comments and corrections - Pickersgill, Martin (Zootaxa, 2008)
In 2007 I published the book “Frog Search—Results of Expeditions to Southern and Eastern Africa”. My aim was to document the results of nearly 10 years of frog research in southern and eastern Africa. It included a number of proposed taxonomic amendments as well as the descriptions of 10 new species. Shortly after publication I realised that one of these new species Phrynobatrachus nigripes Pickersgill, 2007 was in fact the juvenile form of Phrynobatrachus pakenhami Loveridge, 1941. Since I was too late to include errata in the book itself, I take this opportunity to effect this and further amendments and corrections relating to “Frog Search”.